Алгебра 5 дней назад aAlena43

Решить уравнение
-2x(1-x)+3(x-4)=-x(x+2)-6x.

Ответ
1
dobra888

Ответ:   x₁ = - 4 ;   x₂ = 1 .

Объяснение:

      -2x(1-x)+3(x-4)= -x(x+2)-6x ;

      - 2x + 2x² + 3x - 12 = - x² - 2x - 6x ;

      - 2x + 2x² + 3x - 12 + x² + 2x + 6x = 0 ;

        3x² + 9x - 12 = 0 ; │: 3

          x² + 3x - 4 = 0 ;     D = 25 > 0 ;    x₁ = - 4 ;   x₂ = 1 .  

      В - дь :  x₁ = - 4 ;   x₂ = 1 .  

aAlena43: спасибо
Ответ
3
sadykovanatalya2004

Ответ:

-2x(1-x)+3(x-4)=-x(x+2)-6x

-2х+2х²+3х-12=-х²-2х-6х

-2х+2х²+3х-12+х²+2х+6х=0

3х²+9х-12=0

х²+3х-4=0

По теореме Виета:

х1+х2=-3

х1*х2=-4

х1=1

х2=-4

Объяснение:

aAlena43: у вас неправильно в 4 строчке
sadykovanatalya2004: Ага, я уже изменила.Спасибо